Empowered : How IFC Clients Are Financing Climate-Friendly Projects - INTERNATIONAL FINANCE CORPORATION (IFC) (World Bank, Washington, DC, 2022)
IFC, a sister organization of the World Bank and member of the World Bank Group—is the largest global development institution focused on the private sector in emerging markets. IFC estimates that the actions required by the 2015 Paris Agreement will open up about twenty-three trillion in investment opportunities in twenty-one of the largest emerging markets between now and 2030. Most governments lack the capacity to finance the trillions required for their nationally determined contributions (NDCs) to the Paris accords, which is why the private sector including financial institutions has stepped up. Based on IFC’s estimates, about 30 percent of banks’ loan portfolios could be climate-related by 2030, up from 7 percent this day. The stories in this book discuss our Advisory and Investment Services, which help banks to grow, adapt and create markets for climate finance in the countries they serve. This book presents some of the banks that, with IFC’s support, are seizing the market opportunity to make a meaningful contribution to our future.